Implementing ESG Principles in Palm Oil Plantation Management: A Narrative Systematic Review - Hawa Vitria Nur Qholiva; Rahmad Akbar; Nina Veronika (Journal of Current Research in Management, Policy, and Social Studies, 2024)
The palm oil industry faces increasing global pressure to adopt responsible and transparent production systems that address environmental degradation, social inequality, and governance failures. In response, the implementation of Environmental, Social, and Governance (ESG) principles has emerged as a strategic framework for strengthening sustainability performance across plantation operations. This study presents a systematic narrative review of peer-reviewed literature published between 2015 and 2024 to analyze how ESG principles are applied within palm oil plantation management. The review synthesizes empirical findings related to environmental stewardship, social responsibility, and governance reforms, highlighting key trends, progress, and persistent challenges. Results show that ESG implementation contributes significantly to reducing deforestation, improving waste and water management, promoting labor rights, enhancing community engagement, and strengthening institutional transparency through certification and traceability systems. However, structural issues such as inconsistent enforcement, unclear land tenure, socioeconomic disparities, and capacity gaps continue to constrain the effectiveness of ESG adoption. Overall, the findings demonstrate that ESG frameworks, when properly integrated into plantation management, function not only as compliance mechanisms but also as transformative tools capable of elevating the long-term sustainability and legitimacy of the palm oil sector. The study underscores the importance of continued research, multi-stakeholder collaboration, and robust monitoring systems to advance responsible palm oil governance.